2021
DOI: 10.3390/rs13214440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Urban Ecological Quality and Spatial Heterogeneity Based on Remote Sensing: A Case Study of the Rapid Urbanization of Wuhan City

Abstract: Rapid urbanization significantly affects the productivity of the terrestrial ecosystem and the foundation of regional ecosystem services, thereby detrimentally influencing the ecological environment and urban ecological security. The United Nations’ Sustainable Development Goals (SDGs) also require accurate and timely assessments of where people live in order to develop, implement and monitor sustainable development policies. Sustainable development also emphasizes the process of protecting the ecological envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The topography notably influences the distribution and growth of vegetation, and as one of the regions with the highest average altitude worldwide, the drastic topographic fluctuations and harsh climate in Tibet result in locally obvious differences in the vegetation distribution ( Wang et al, 2019 , 2022 ). Spatial autocorrelation can reveal whether and to what extent the attribute characteristics of neighboring elements in geographic space are related and has become a common method for the study of vegetation growth, carbon cycle, heat island effect, and other changes in vegetation ecology and the environment ( Li et al, 2021 ; Yang et al, 2021 ). Global Moran’s index and local Moran’s index were used to detect the aggregation and local effects of the vegetation NDVI in Tibet, and the results revealed that the NDVI experienced high spatial agglomeration from 2001 to 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topography notably influences the distribution and growth of vegetation, and as one of the regions with the highest average altitude worldwide, the drastic topographic fluctuations and harsh climate in Tibet result in locally obvious differences in the vegetation distribution ( Wang et al, 2019 , 2022 ). Spatial autocorrelation can reveal whether and to what extent the attribute characteristics of neighboring elements in geographic space are related and has become a common method for the study of vegetation growth, carbon cycle, heat island effect, and other changes in vegetation ecology and the environment ( Li et al, 2021 ; Yang et al, 2021 ). Global Moran’s index and local Moran’s index were used to detect the aggregation and local effects of the vegetation NDVI in Tibet, and the results revealed that the NDVI experienced high spatial agglomeration from 2001 to 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The Hurst exponent method based on rescaled interval (R/S) analysis is a time-series analysis method based on fractal theory and exhibits wide applications in the fields of climate change and population migration ( Peng et al, 2012 ). R/S analysis can measure how the fluctuation range of a given time series varies with the time span, which can be used to predict the future trend of vegetation ( Jiang et al, 2015 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The entropy weight method has been used in recent analysis of the ecological quality of the terrestrial system using remote sensing monitoring [61]. The advantage of this method is that it is an objective multi-index evaluation to attain the relative intensity of each index solely based on the information that each index contains.…”
Section: Effectiveness Score Calculationmentioning
confidence: 99%
“…The rationale behind this weighting method is that the weight of each of the three sub-metrics mentioned above could be determined using the information provided from their observation values. Details regarding the entropy weight method are listed as follows [61]:…”
Section: Effectiveness Score Calculationmentioning
confidence: 99%
“…Since RSEI was developed, it has been applied in ecological quality assessment of cities [20], basins [21], nature reserves [22], and various regions around the world. Some research even improves the model to make it more suitable for specific regions [23]. Generally, applications proved the feasibility and efficiency of RSEI.…”
Section: Introductionmentioning
confidence: 99%